Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T11:09:48+01:00
(x-1)(x-1)(x-3)(x²-2x-6)=(x-1)²(x-3)(x²-2x-6)
Δ=-2²x((-6)x(-4))=28
√Δ=√28=2√7
x₁=(2-2√7)/2=1-√7
x₂=(2+2√7)/2=1+√7

(x-1)(x-1)(x-3)(x-1-√7)(x-1+√7)

:) Wszystko schematem Hornera
2009-11-22T11:14:30+01:00
Znajdź pierwiastki wielomianu
x⁵-7x⁴+11x³+13x²-36x+18<0
W(1)=0
zatem z Hornera

(x-1)(x-1)(x-3)(x²-2x-6)=(x-1)²(x-3)(x²-2x-6)=
=(x-1)(x-1)(x-3)(x-1-√7)(x-1+√7)


x²-2x-6=0

Δ=-2²x[(-6)*(-4)]=28
√Δ=√28=2√7
x₁=(2-2√7)/2=1-√7
x₂=(2+2√7)/2=1+√7